Gestión administrativa Municipal de Puente Piedra, según percepción de los trabajadores de la Gerencia de Inversiones Públicas, Lima-2018 - Vega Polo, Fany Mildred (2019)
The present investigation has as a study variable Administrative management. Its general objective was to determine the level of effectiveness in the Municipal Administrative Management of Puente Piedra, according to the perception of the workers of the Public Investment Management, Lima-2018. The research carried out was of a quantitative approach, basic type of descriptive level, non-experimental cross-sectional design. The population was made up of 50 employees, who were interviewed as a census. The data collection was carried out with the survey technique and the instrument was a questionnaire, information was collected on the variable under study, the data collection instrument was validated by experts with a result of applicability, the reliability was determined by the Alpha Crombach coefficient whose value was 0.891 for the variable In accordance with the results obtained from the survey of the 50 workers of the Management of Public Inversions of the District Municipality of Puente Piedra it was observed that 94.00% of the respondents consider that the municipal administrative management of Puente Piedra is effective while 6.00% of respondents I see it as very effective.